Romanisierung als Integrationsfaktor des Imperium Romanum - Mrozewicz, Leszek (Studia Europaea Gnesnensia, 2017)
Romanization is one of the most cultural phenomena of the Roman world, whose distant echoes are palpable even today. It should be construed as a consolidation of the image of the Roman state throughout its territory, while taking local cultural components into account. It was not directed and controlled from above; on the contrary, it should be approached as a grassroots process, by and large a spontaneous one. It was not straightforward and direct either, as Roman culture was disseminated and consolidated via a secondary, or „second-hand” impact.